High-heat-resistance microwave bonding sheet, preparation method and copper-clad plate manufactured by using high-heat-resistance microwave bonding sheet
By combining the modified polyphenylene ether resin with other double bond components, a high heat-resistant microwave bonding sheet is formed, and combined with vacuum curing technology, the problem of layering, explosive plates and bubbles of high-frequency copper clad plates when heated is solved, and copper clad plates with high thermal reliability and excellent dielectric properties are achieved.
Patent Information
- Application Number
- CN202411836393.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
Smart Images

Figure BDA0005186815240000011 
Figure BDA0005186815240000101 
Figure BDA0005186815240000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of copper clad laminates, and in particular to a high-heat-resistant microwave adhesive sheet, a preparation method and a copper clad laminate made using the same. Background Art
[0002] PTFE / ceramic microwave composite dielectric substrate materials have been used in military, aerospace and other communication fields due to their excellent high-frequency and low-loss characteristics and stable dielectric constant. Since the 1990s, with the development of civilian radio frequency communication technology, PTFE has also begun to be widely used in base station antennas, automotive radars and various radio frequency devices, and its market demand has increased year by year.
[0003] In recent years, the vigorous development of industries such as 5G communication technology, the Internet of Things, and new energy vehicles has promoted the transformation and upgrading of the copper clad laminate industry to high frequency and high speed, prompting the matrix resin adapted to high-frequency applications to become the key research direction of today's material manufacturers. Among them, hydrocarbon resin has good low dielectric and low loss properties due to its extremely low molecular polarity, making it a high-frequency and high-speed copper clad laminate substrate with extremely low / ultra-low loss (dielectric loss Df<0.005). However, as a thermoplastic resin, hydrocarbon resin can flow and deform after being heated, and has problems such as low mechanical strength and insufficient thermal performance. Therefore, it is necessary to enhance and modify it, and form a highly cross-linked interpenetrating polymer network structure through the cross-linking reaction of unsaturated double bonds in the molecule, so that it can be transformed from a thermoplastic to a thermosetting resin, thereby improving the mechanical strength and high temperature resistance of hydrocarbon resin materials. The hydrocarbon resin used for high-frequency copper-clad laminate substrates is usually a polyolefin homopolymer or copolymer, such as one or a mixture of two or more of polybutadiene, polyisoprene, styrene-butadiene copolymer, styrene-isoprene copolymer, styrene-divinylbenzene copolymer, polystyrene and other polymers, among which the most typical is the high vinyl polybutadiene (1,2-polybutadiene) system.
[0004] Bifunctional acrylic end-capped polyphenylene ether oligomers are very suitable for free radical polymerization with other unsaturated monomers or resins, including styrene, allyl, acrylic acid, maleimide, methacrylic acid and unsaturated polyester monomers and resins. They also have excellent solubility and low viscosity in toluene and butanone. They are mainly used in electronic packaging materials, including PCB substrates, copper-clad laminates, non-epoxy system prepregs and adhesives. This product is designed for ultra-low dielectric and low water absorption applications. Methyl methacrylate modified polyphenylene ether is a commonly used polyphenylene ether resin, and its molecular structure is shown below:
[0005]
[0006] Methyl methacrylate modified polyphenylene ether can be used in copper clad laminates and prepregs for high-frequency and high-speed circuits. The functionalized acrylic end groups can ensure efficient reaction between PPO and crosslinking agents. Methyl methacrylate modified polyphenylene ether can also be used in other composite materials, such as hydrocarbon resins: styrene-butadiene block copolymers, styrene-isoprene block copolymers, 1,2-polybutadiene, 1,4-polybutadiene, maleic acid modified polybutadiene, acrylic acid modified polybutadiene, and epoxy modified polybutadiene.
[0007] Methyl methacrylate modified polyphenylene ether resin reacts easily with TAIC resin to form a single-phase network. In general, the incorporation of methyl methacrylate modified polyphenylene ether resin into the triazine matrix can prepare polymers with high glass transition temperature (>200°C), low dielectric properties and other performance advantages, especially the significant improvement of toughness and tensile strength. In addition, the hygroscopicity is also significantly reduced. The reduced hygroscopicity can effectively reduce the fluctuation of dielectric properties caused by moisture, thereby having more stable dielectric properties. Polyphenylene oxide (PPO for short) is an engineering plastic with very excellent performance. It has a rigid skeleton chain and polar groups, so it has excellent mechanical properties, heat resistance, water resistance, flame retardancy and good dimensional stability, and has high glass transition temperature (Tg) and low dielectric constant (Dk), low dielectric loss (Df) and other properties, so it has great application potential in high-frequency and high-speed copper clad laminates. Generally, commercialized PPO has the disadvantages of high molecular weight, poor fluidity, and high molding temperature, which limits its application in the field of CCL to a certain extent. Therefore, PPO needs to be modified. If the epoxy group is introduced using the terminal hydroxyl group, a low molecular weight PPO containing an epoxy group can be prepared. Then the modified PPO is epoxidized, and it is found that the modified PPO has good compatibility with EP, and the prepared CCL has good dielectric properties. Asahi Kasei of Japan introduced allyl groups into the main chain of the PPO molecule, and for the first time achieved the thermal curing of polyphenylene ether itself. If the epoxy resin is modified with redistributed PPO, a high heat resistance and low dielectric CCL can be prepared. The PPO / EP system can also be prepared with epoxy-terminated PPO. It will be found that the system has good compatibility and the prepared CCL has excellent thermal expansion. If a low molecular weight PPO (R-PPO) is synthesized by redistribution of maleic anhydride and PPO, and the epoxy resin is modified with it, the dielectric properties of EP are successfully improved. Related research has prepared high molecular weight PPO into low molecular weight PPO through redistribution reaction, and then epoxidized it, and then added it to the low dielectric DCPD epoxy / active ester system, and then prepared the corresponding copper clad laminate after impregnating the semi-cured sheet. Summary of the invention
[0008] The technical problem to be solved by the present invention is to overcome the defects of the prior art. The present invention proposes a high-heat-resistant microwave adhesive sheet, a preparation method and a copper-clad laminate made using the same, which improve the undesirable performance of traditional high-frequency adhesive sheets combined with PTFE substrates, such as easy delamination, bursting and bubbles when heated.
[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a high heat-resistant microwave adhesive sheet, which is specifically as follows: uniformly coating the prepared adhesive liquid on both sides of the ceramic filler film, hanging the ceramic film on the surface of the adhesive liquid, and then placing it in an oven and baking it at 120°C for 5 minutes to obtain the adhesive sheet;
[0010] The glue solution comprises, by weight, 9-11 parts of modified polyphenylene ether resin, 4-7 parts of toughening agent, 2-8 parts of elastomer, 2-3 parts of crosslinking agent, 24-68 parts of filling material, 0.05-0.44 parts of initiator and 35-50 parts of toluene;
[0011] The low molecular weight polyphenylene ether is methyl methacrylate modified polyphenylene ether.
[0012] Furthermore, the elastomer includes at least one of XPH-201R, A1535, H1043, SBS-A and P2000.
[0013] Furthermore, the toughening agent is any one of B300, MA75 and 1,2-SBS or a combination of two thereof.
[0014] Further, the filling material includes 4-5 parts of flame retardant and 20-63 parts of spherical silicon;
[0015] The flame retardant is any one of mosaflam and SAYTEX-8010; the spherical silicon is any one of SE0047, SE0043 and Q099.
[0016] Furthermore, during the preparation process, the 1,2-SBS and A1535 were baked at 50° C. for 15 minutes and then dissolved in toluene.
[0017] Furthermore, the glue solution also includes 0.2 parts of a silane coupling agent, the coupling agent is KBM-503, the cross-linking agent is TAIC, and the initiator is BIBP.
[0018] Furthermore, a high heat-resistant microwave adhesive sheet is prepared according to the following steps:
[0019] S1, adding a solvent, a toughening agent, an elastomer, a modified polyphenylene ether resin and a cross-linking agent in sequence and mixing them, adding a filler material and an initiator to the obtained mixture, stirring and homogenizing the obtained glue;
[0020] S2. The ceramic filler sodium film is glued with the glue liquid by an impregnation process, and then baked in an oven at 120° C. for 300 seconds to obtain a bonding sheet.
[0021] Furthermore, a high heat-resistant microwave copper-clad laminate is prepared using a high heat-resistant microwave adhesive sheet, and the preparation method thereof is as follows:
[0022] The baked bonding sheet is cut according to RC, and after copper foil is coated on both sides of the bonding sheet, a plurality of bonding sheets are stacked and placed in a press to complete the plate pressing process.
[0023] Furthermore, in the pressing process, the multi-layer bonding sheet is pressed into a copper-clad laminate under a vacuum degree of -0.106 MPa and a pressure of 261-564 psi, with the temperature of the hot plate adjusted to 150-220° C. and the curing time being 200 min.
[0024] Compared with the prior art, the beneficial effects of the present invention include: by applying modified polyphenylene ether resin in combination with other different components containing double bonds to form a resin prepolymer, it has high reliability, low dielectric properties and excellent compatibility. The prepared bonding sheet has a low expansion coefficient, low dielectric properties, excellent moisture and heat resistance and high thermal reliability, so that the bonding sheet pressed onto the PTFE core board has a very intuitive and better performance in the reflow soldering test, and there is no delamination, bursting, bubbles and other undesirable performance after heating. DETAILED DESCRIPTION
[0025] It is easy to understand that according to the technical solution of the present invention, without changing the essential spirit of the present invention, a person skilled in the art can propose a variety of interchangeable structural modes and implementation modes. Therefore, the following specific implementation modes are only exemplary descriptions of the technical solution of the present invention, and should not be regarded as the whole of the present invention or as a limitation or restriction to the technical solution of the present invention.
[0026] A method for preparing a high heat-resistant microwave adhesive sheet, specifically comprising: uniformly coating the prepared adhesive liquid on both sides of a ceramic filler film, impregnating the ceramic film on the adhesive liquid surface and hanging it on a drying rack, and then placing it in an oven and baking it at 120° C. for 5 minutes to obtain an adhesive sheet;
[0027] The aforementioned adhesive solution comprises, by weight, 9-11 parts of low molecular weight polyphenylene ether, 2-8 parts of elastomer, 20-63 parts of filler, 5 parts of flame retardant, 2-3 parts of crosslinking agent, 4-7 parts of toughening agent, 0.2 parts of silane coupling agent, 0.05-0.44 parts of initiator and 35-50 parts of toluene; during the preparation process, the aforementioned low molecular weight polyphenylene ether, elastomer, filler, flame retardant, crosslinking agent, toughening agent, silane coupling agent and initiator are dissolved in toluene to form an adhesive solution.
[0028] The following is an explanation of the raw material information:
[0029] Modified polyphenylene ether resin: methyl methacrylate modified polyphenylene ether SA9000, Saudi Basic Industries Corporation (Sabic);
[0030] TAIC: triallyl isocyanurate, Evonik;
[0031] A1535: Transparent linear triblock copolymer of styrene and ethylene / butylene (dielectric loss below 0.001), Kraton High Performance Polymers, USA;
[0032] SBS-A: high molecular weight block copolymer (molecular weight 20000-30000), Nippon Soda Co., Ltd.;
[0033] 1,2-SBS: high 1,2-vinyl content styrene / butadiene / styrene block copolymer (1,2-vinyl content greater than 90%), Nippon Soda Co., Ltd.
[0034] H1043: Fully hydrogenated styrene thermoplastic elastomer, Asahi Kasei Corporation;
[0035] MA75: Maleic anhydride modified liquid polybutadiene rubber, Evonik, Germany;
[0036] B3000: Polystyrene-butadiene copolymer toughening agent, Japan Soda Co., Ltd.;
[0037] P2000: Selectively hydrogenated styrene-based thermoplastic elastomer, Asahi Kasei Corporation;
[0038] PX200: 1,3-phenylene phosphate tetrakis (2,6-dimethylphenyl) ester (condensation polymer), Daihachi Chemical Industry Co., Ltd.;
[0039] Mosaflam506: Additive phosphorus flame retardant, Suzhou Zhonghe New Chemical;
[0040] XPH-201R: block polymer, Kraton High Performance Polymers, Inc., USA;
[0041] EQ2405-SMC: phenylamino type D50 two-micron spherical silica, Huzhou Sanshiji;
[0042] SE0043: phenylamino type D502μm spherical silica, Suzhou Jinyi;
[0043] BIBP: di-tert-butyl peroxide diisopropylbenzene, Shanghai Sendi Chemical;
[0044] Reinforcement material: PTFE reinforced ceramic filler sodium membrane, Nanjing Kent Composite Materials Co., Ltd.; or PTFE reinforced ceramic filler membrane, Ruilong self-made (thickness: 60±5μm; DK: 2.50±0.03; DF: 0.0015±0.0005; tensile strength: ≥8Mpa; elongation at break: ≥150%; surface tension: ≥42dyn / cm)
[0045] Copper foil: Luxembourg TWS copper foil.
[0046] After the baked bonding sheet is cut according to RC, copper foil is coated on both sides of the bonding sheet. After stacking multiple bonding sheets, they are placed in a press to complete the pressing process to obtain a copper-clad laminate.
[0047] By introducing high heat-resistant low molecular weight modified polyphenylene ether resin into the formula of high heat-resistant microwave multilayer adhesive sheet, and matching it with other different components with double bonds for balance and optimization, curing is completed by free radical polymerization. Since the free radical curing product does not produce new polar groups, it can well improve the electrical properties of the polyphenylene ether structure itself. In addition, due to its own dense and regular benzene ring structure, the resin system also has good heat resistance and thermal expansion coefficient, thereby greatly improving the pure hydrocarbon main system resin microwave multilayer adhesive sheet that is not heat-resistant, and has the undesirable phenomena of bursting, delamination and bubbling when encountering high heat, thereby increasing the reliability of the material; and the addition of polyphenylene ether can also play an excellent optimization role in the dielectric properties of the entire adhesive sheet product after pressing.
[0048] The technical effects of the present invention are further described below in conjunction with embodiments.
[0049] Comparative Example-1 The specific implementation steps are:
[0050] Glue preparation: Take an empty and clean 1000ml polypropylene wide-mouth bottle as a mixing glue carrier container, first add 100g of solvent toluene into the container, weigh 10g of elastomer 5 (low dielectric loss block polymer, Kraton High Performance Polymers Co., Ltd., USA) and 20g of elastomer 3 (fully hydrogenated styrene thermoplastic elastomer, Asahi Kasei Corporation) on an electronic balance, add them to the carrier container in sequence, start slow stirring at 500rpm, and continue stirring for 60 minutes until the elastomer is completely dissolved and transparent; place toughener 1 (high 1,2-vinyl content styrene / butadiene / styrene block copolymer, Japan Soda Co., Ltd.) in a constant temperature oven at 50°C, bake for 15 minutes, weigh 35g and add it to the pre-dissolved container wide-mouth bottle, and use a rubber-tipped dropper to drop 15g of the cross-linking agent (triallyl isocyanurate, Evonik Industries (Evonik);) into the pre-dissolved container wide-mouth bottle, and Add 50g of solvent toluene, start slow stirring at 500rpm, and continue stirring for 30 minutes until the toughening agent is completely dissolved; weigh 5g of flame retardant 1 (1,3-phenylene tetrakis (2,6-dimethylphenyl) phosphate (condensation polymer), Daihachi Chemical Industry Co., Ltd.), 20g of flame retardant 2 (additive phosphorus flame retardant, Suzhou Zhonghe New Chemical), 100g of filler 2 (acrylic-based treated D50 two-micron spherical silica, Suzhou Jinyi), and 0.25g of initiator (di-tert-butyl peroxide diisopropylbenzene, Shanghai Sendi (Shendi) Chemical Industry), and add them to the pre-dissolved pre-dissolved container wide-mouth bottle in turn, and add 50g of solvent toluene, start rapid stirring at 1200rpm, and continue stirring for 90 minutes. When the glue is completely mixed, transfer it to a high shear emulsifier (brand: FLUKO), set the speed to 10000rpm, and the time to 10min. The glue mixing is complete.
[0051] Coating: Add the prepared glue into a simple coating device used in the laboratory. The coating carrier is Ruilong's homemade 63μm PTFE ceramic filler membrane. Make the reinforced material evenly covered with a layer of the mixed glue on both sides. After the wet impregnated ceramic membrane is hung on the drying rack for 10 minutes, the coating is completed and ready for baking.
[0052] Baking: Set the baking temperature of the automatic constant temperature oven to 120°C, slowly move the coated adhesive sheet into the oven, set the baking time to 5 minutes, and the baking is complete.
[0053] Pressing plate: Cut the baked adhesive sheet into 9×12 inch size, weigh and calculate the RC of the adhesive sheet, select four sheets with uniform RC of about 50% for combination, cover each side with a piece of Luxembourg TWS copper foil with a thickness of 35μm, completely cover the four combined and stacked adhesive sheets, put them into the press (the press is Xianyang Weidi small hot oil press), the buffer material is 15 pieces of kraft paper, and the pressing plate parameters include: vacuum degree -0.106Mpa, pressure 261psi-564psi, hot plate temperature 150℃-220℃, curing time 200min. The copper-clad laminate is made and the pressing plate is completed.
[0054] Sample preparation test: After the pressing is completed, sampling test is carried out. The relevant test methods and processes have been elaborated in detail in the above analytical test methods. The test results are shown in Table 1.
[0055] Embodiment-2 The specific implementation steps are:
[0056] Glue preparation: Take an empty and clean 1000ml polypropylene wide-mouth bottle as a mixing container, first add 100g of solvent toluene into the container, weigh 10g of elastomer 1 (transparent linear triblock copolymer of styrene and ethylene / butylene, Kraton High Performance Polymers, USA) and 20g of elastomer 3 (fully hydrogenated styrene-based thermoplastic elastomer, Asahi Kasei Corporation) on an electronic balance, add them to the carrier container in sequence, start slow stirring at 500rpm, and continue stirring for 60 minutes until the elastomer is The body is completely dissolved and transparent; toughener 3 (polystyrene-butadiene copolymer toughener, Japan Soda Co., Ltd.) is placed in a constant temperature oven at 50°C and baked for 15 minutes, 25g is weighed and added to a pre-dissolved container wide-mouth bottle, toughener 2 (maleic anhydride modified liquid polybutadiene rubber, Germany Evonik;) is weighed 10g and added to a pre-dissolved container wide-mouth bottle, and 50g of solvent toluene is added, and slow stirring is turned on, the speed is 500rpm, and stirring is continued for 30 minutes until the toughener is completely dissolved; low molecular weight polyphenylene ether 5 is weighed with an electronic balance 5g was poured into a pre-dissolved container wide-mouth bottle, 10g of the cross-linking agent (triallyl isocyanurate, Evonik Industries (Evonik);) was dripped into the pre-dissolved container wide-mouth bottle with a rubber-tipped dropper, and 100g of solvent toluene was added, and slow stirring was started at a speed of 500rpm, and stirring was continued for 60 minutes until it was completely dissolved; 25g of flame retardant 3 (additive brominated flame retardant, decabromodiphenylethane, Yabao Chemical) and 315g of filler 3 (phenylamino type D50 three-micron spherical silica, Suzhou Jinyi;) were weighed, and initiator (Di-tert-butyl peroxide diisopropylbenzene, Shanghai Sendi (Shendi) Chemical Industry;) 2.2g, add it into the pre-dissolved pre-dissolved container wide-mouth bottle in turn, and use a rubber-tipped dropper to drop 1ml of coupling agent (silane coupling agent, Evonik, Germany;) and add it, add 50g of solvent toluene, start rapid stirring at a speed of 1200rpm, and continue stirring for 90 minutes. When the glue is completely mixed, transfer it to a high shear emulsifier (brand: FLUKO), set the speed to 10000rpm, and the time to 10min, and the glue mixing is completed.
[0057] Coating: Add the prepared glue into a simple coating device used in the laboratory. The coating carrier is Ruilong's homemade 63μm PTFE ceramic filler membrane. Make the reinforced material evenly covered with a layer of the mixed glue on both sides. After the wet impregnated ceramic membrane is hung on the drying rack for 10 minutes, the coating is completed and ready for baking.
[0058] Baking: Set the baking temperature of the automatic constant temperature oven to 120°C, slowly move the coated adhesive sheet into the oven, set the baking time to 5 minutes, and the baking is complete.
[0059] Pressing plate: Cut the baked adhesive sheet into 9×12 inch size, weigh and calculate the RC of the adhesive sheet, select four sheets with uniform RC of about 50% for combination, cover each side with a piece of Luxembourg TWS copper foil with a thickness of 35μm, completely cover the four combined and stacked adhesive sheets, put them into the press (the press is Xianyang Weidi small hot oil press), the buffer material is 15 pieces of kraft paper, and the pressing plate parameters include: vacuum degree -0.106Mpa, pressure 261psi-564psi, hot plate temperature 150℃-220℃, curing time 200min. The copper-clad laminate is made and the pressing plate is completed.
[0060] Sample preparation test: After the pressing is completed, sampling test is carried out. The relevant test methods and processes have been elaborated in detail in the above analytical test methods. The test results are shown in Table 1.
[0061] Embodiment-3 The specific implementation steps are:
[0062] Glue preparation: Take an empty and clean 1000ml polypropylene wide-mouth bottle as a glue mixing carrier container, first add 100g of solvent toluene into the container, weigh 10g of elastomer 5 (low dielectric loss block polymer, Kraton High Performance Polymers Co., Ltd., USA) and 20g of elastomer 2 (high molecular weight SBS block copolymer, Japan Soda Co., Ltd.) on an electronic balance, add them to the carrier container in sequence, start slow stirring at a speed of 500rpm, and continue stirring for 60 minutes until the elastomer is completely dissolved and transparent; use an electronic balance to weigh 55g of low molecular weight polyphenylene ether and pour it into a pre-dissolving container wide-mouth bottle, use a rubber-tipped dropper to drop 15g of a cross-linking agent (triallyl isocyanurate, Evonik Industries (Evonik);) into the pre-dissolving container wide-mouth bottle, and add 50g of solvent toluene, start slow stirring at a speed of 500rpm, and continue stirring for 60 minutes. Continue stirring for 60 minutes until the solid resin is completely dissolved; weigh 5g of flame retardant 1 (1,3-phenylene tetrakis (2,6-dimethylphenyl) phosphate (condensation polymer), Daihachi Chemical Industry Co., Ltd.), 20g of flame retardant 2 (additive phosphorus flame retardant, Suzhou Zhonghe New Chemical), 100g of filler 2 (acrylic-based treated D50 two-micron spherical silica, Suzhou Jinyi), and 0.25g of initiator (di-tert-butyl peroxide diisopropylbenzene, Shanghai Sendi (Shendi) Chemical Industry), and add them to the pre-dissolved pre-dissolved container wide-mouth bottle in turn, and add 45g of solvent toluene, start rapid stirring, the speed is 1200rpm, and the stirring is continued for 90 minutes. When the glue is completely mixed, transfer it to a high shear emulsifier (brand: FLUKO), set the speed to 10000rpm, the time is 10min, and the glue mixing is completed.
[0063] Coating: Add the prepared glue into a simple coating device used in the laboratory. The coating carrier is Ruilong's homemade 63μm PTFE ceramic filler membrane. Make the reinforced material evenly covered with a layer of the mixed glue on both sides. After the wet impregnated ceramic membrane is hung on the drying rack for 10 minutes, the coating is completed and ready for baking.
[0064] Baking: Set the baking temperature of the automatic constant temperature oven to 120°C, slowly move the coated adhesive sheet into the oven, set the baking time to 5 minutes, and the baking is complete.
[0065] Pressing plate: Cut the baked adhesive sheet into 9×12 inch size, weigh and calculate the RC of the adhesive sheet, select four sheets with uniform RC of about 50% for combination, cover each side with a piece of Luxembourg TWS copper foil with a thickness of 35μm, completely cover the four combined and stacked adhesive sheets, put them into the press (the press is Xianyang Weidi small hot oil press), the buffer material is 15 pieces of kraft paper, and the pressing plate parameters include: vacuum degree -0.106Mpa, pressure 261psi-564psi, hot plate temperature 150℃-220℃, curing time 200min. The copper-clad laminate is made and the pressing plate is completed.
[0066] Sample preparation test: After the pressing is completed, sampling test is carried out. The relevant test methods and processes have been elaborated in detail in the above analytical test methods. The test results are shown in Table 1.
[0067] Embodiment-4 The specific implementation steps are:
[0068] 10 g of Elastomer 1 (a transparent linear triblock copolymer of styrene and ethylene / butylene, Kraton Performance Polymers, Inc., USA) was used to replace 10 g of Elastomer 5 (a low dielectric loss block polymer, Kraton Performance Polymers, Inc., USA) in Example-3.
[0069] 20 g of Elastomer 4 (selectively hydrogenated styrene-based thermoplastic elastomer, Asahi Kasei Corporation;) was used in place of Elastomer 2 (high molecular weight SBS block copolymer, Nippon Soda Co., Ltd.;) in Example-3.
[0070] The other conditions were the same as those in Example 3, and a copper-clad laminate was prepared. Samples were prepared and tested, and the test results are shown in Table 1.
[0071] Embodiment-5 The specific implementation steps are:
[0072] Glue preparation: Take an empty and clean 1000ml polypropylene wide-mouth bottle as a glue mixing carrier container, first add 100g of solvent toluene into the container, weigh 20g of elastomer 5 (low dielectric loss block polymer, Kraton High Performance Polymers Co., Ltd., USA) and 20g of elastomer 2 (high molecular weight SBS block copolymer, Japan Soda Co., Ltd.) on an electronic balance, add them to the carrier container in sequence, start slow stirring at a speed of 500rpm, and continue stirring for 60 minutes until the elastomer is completely dissolved and transparent; weigh 45g of low molecular weight polyphenylene ether with an electronic balance and pour it into a pre-dissolving container wide-mouth bottle, take 15g of the cross-linking agent (triallyl isocyanurate, Evonik Industries (Evonik);) with a rubber-tipped dropper and add it to the pre-dissolving container wide-mouth bottle, and add 50g of solvent toluene, start slow stirring at a speed of 500rpm, Continue stirring for 60 minutes until the solid resin is completely dissolved; weigh 5g of flame retardant 1 (1,3-phenylene tetrakis (2,6-dimethylphenyl) phosphate (condensation polymer), Daihachi Chemical Industry Co., Ltd.), 20g of flame retardant 2 (additive phosphorus flame retardant, Suzhou Zhonghe New Chemical), 100g of filler 1 (vinyl-treated D50 two-micron spherical silica, Suzhou Jinyi), 0.25g of initiator (di-tert-butyl peroxide diisopropylbenzene, Shanghai Sendi (Shendi) Chemical Industry), and add them to the pre-dissolved pre-dissolved container wide-mouth bottle in turn, and add 45g of solvent toluene, start rapid stirring, the speed is 1200rpm, and the stirring is continued for 90 minutes. When the glue is completely mixed, transfer it to a high shear emulsifier (brand: FLUKO), set the speed to 10000rpm, the time is 10min, and the glue mixing is completed.
[0073] Coating: Add the prepared glue into a simple coating device used in the laboratory. The coating carrier is Ruilong's homemade 63μm PTFE ceramic filler membrane. Make the reinforced material evenly covered with a layer of the mixed glue on both sides. After the wet impregnated ceramic membrane is hung on the drying rack for 10 minutes, the coating is completed and ready for baking.
[0074] Baking: Set the baking temperature of the automatic constant temperature oven to 120°C, slowly move the coated adhesive sheet into the oven, set the baking time to 5 minutes, and the baking is complete.
[0075] Pressing plate: Cut the baked adhesive sheet into 9×12 inch size, weigh and calculate the RC of the adhesive sheet, select four sheets with uniform RC of about 50% for combination, cover each side with a piece of Luxembourg TWS copper foil with a thickness of 35μm, completely cover the four combined and stacked adhesive sheets, put them into the press (the press is Xianyang Weidi small hot oil press), the buffer material is 15 pieces of kraft paper, and the pressing plate parameters include: vacuum degree -0.106Mpa, pressure 261psi-564psi, hot plate temperature 150℃-220℃, curing time 200min. The copper-clad laminate is made and the pressing plate is completed.
[0076] Sample preparation test: After the pressing is completed, sampling test is carried out. The relevant test methods and processes have been elaborated in detail in the above analytical test methods. The test results are shown in Table 1.
[0077] The specific implementation steps of Example-6 are:
[0078] Glue preparation: Take an empty and clean 1000ml polypropylene wide-mouth bottle as a mixing glue carrier container, first add 100g of solvent toluene into the container, weigh 10g of elastomer 5 (low dielectric loss block polymer, Kraton High Performance Polymers Co., Ltd., USA) on an electronic balance, add it to the carrier container, start slow stirring at 500rpm, and continue stirring for 60 minutes until the elastomer is completely dissolved and transparent; place toughening agent 1 (high 1,2-vinyl content styrene / butadiene / styrene block copolymer, Japan Soda Co., Ltd.) in a constant temperature oven at 50°C, bake for 15 minutes, weigh 20g and add it to the pre-dissolved container wide-mouth bottle, use an electronic balance to weigh 55g of low molecular weight polyphenylene ether and pour it into the pre-dissolved container wide-mouth bottle, use a rubber-tipped dropper to drip 15g of cross-linking agent (triallyl isocyanurate, Evonik Industries (Evonik);) into the pre-dissolved container wide-mouth bottle, and add 5g of solvent toluene. 0g, start slow stirring, speed 500rpm, continue stirring for 60 minutes until the toughening agent and solid resin are completely dissolved; weigh flame retardant 1 (1,3-phenylene phosphate tetrakis (2,6-dimethylphenyl) ester (condensation polymer), Daihachi Chemical Industry Co., Ltd.);) 5g, flame retardant 2 (additive phosphorus flame retardant, Suzhou Zhonghe New Chemical;) 20g, filler 2 (acrylic-based treated D50 two-micron spherical silica, Suzhou Jinyi;) 105g, initiator (di-tert-butyl peroxide diisopropylbenzene, Shanghai Sendi (Shendi) Chemical;) 0.25g, add them into the above-mentioned pre-dissolved pre-dissolved container wide-mouth bottle in sequence, and add 25g of solvent toluene, start rapid stirring, speed 1200rpm, continue stirring for 90 minutes, wait for the glue to be completely mixed, transfer to a high shear emulsifier (brand: FLUKO), set the speed to 10000rpm, time 10min, and the glue mixing is completed.
[0079] Coating: Add the prepared glue into a simple coating device used in the laboratory. The coating carrier is Ruilong's homemade 63μm PTFE ceramic filler membrane. Make the reinforced material evenly covered with a layer of the mixed glue on both sides. After the wet impregnated ceramic membrane is hung on the drying rack for 10 minutes, the coating is completed and ready for baking.
[0080] Baking: Set the baking temperature of the automatic constant temperature oven to 120°C, slowly move the coated adhesive sheet into the oven, set the baking time to 5 minutes, and the baking is complete.
[0081] Pressing plate: Cut the baked adhesive sheet into 9×12 inch size, weigh and calculate the RC of the adhesive sheet, select four sheets with uniform RC of about 50% for combination, cover each side with a piece of Luxembourg TWS copper foil with a thickness of 35μm, completely cover the four combined and stacked adhesive sheets, put them into the press (the press is Xianyang Weidi small hot oil press), the buffer material is 15 pieces of kraft paper, and the pressing plate parameters include: vacuum degree -0.106Mpa, pressure 261psi-564psi, hot plate temperature 150℃-220℃, curing time 200min. The copper-clad laminate is made and the pressing plate is completed.
[0082] Sample preparation test: After the pressing is completed, sampling test is carried out. The relevant test methods and processes have been elaborated in detail in the above analytical test methods. The test results are shown in Table 1.
[0083] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0084] Scale up the actual amount of addition in proportion to the weight as shown in the table above, and add the actual materials by gram weight. Add the solvent, toughening agent, elastomer, modified polyphenylene ether resin and cross-linking agent in turn, turn on the high-speed agitator at a speed of 1000rpm, and continue stirring for 60 minutes until the resin is completely dissolved, and the flashlight shines directly on it to show a clear and transparent state; then add the filling material, such as adding different types of flame retardants and spherical silicon as shown in the table above, and stir at a speed of 1000rpm for 30 minutes; weigh the initiator and add it to the evenly mixed glue, and then stir at a speed of 1000rpm for 20 minutes. Use a homogenizer to homogenize the glue for 10 minutes, and the glue adjustment is completed.
[0085] Put the homogenized glue into the glue tank, apply glue to our reinforcement material 63μm ceramic filler sodium film through the dipping process, put it in the oven and bake it at 120℃ for 300s to obtain the bonding sheet; cut the bonding sheet into the same size (for example: 9×12inch), 4 sheets in a group, overlap the bonding sheets, cover 1oz thick Luxembourg TWS copper foil on both sides, vacuum cure in the press to make copper-clad laminate, and then press to make metal foil-clad laminate. The pressing parameters include: vacuum degree -0.106Mpa, pressure 261psi-564psi, hot plate temperature 150℃-220℃, and curing time 200min.
[0086] The component properties of the aforementioned comparative examples and embodiments are specifically shown in Table 1 below:
[0087] Table 1: Experimental component performance list
[0088]
[0089]
[0090] Note: The added materials in the comparative examples and examples described in Table 1 are the simplest weight proportions; the detailed introduction of the components is given in detail in the main raw materials of the technical scheme.
[0091] 4.3 Performance analysis;
[0092] The Z-axis thermal expansion coefficient of the metal foil plate prepared by the resin composition glue of the present invention is less than 100ppm / K, such as Examples 3, 4, and 6. It has good dimensional stability and good mechanical processing performance, and is easy to process in the board factory; in terms of heat resistance: T300>60min, PCT high pressure steaming and tinning without board explosion, copper-containing board hot tinning for 15min without board explosion, and PTFE substrate core board pressed 4-layer board without blistering after reflow soldering, such as Examples 2-6; in terms of electrical properties: dielectric constant (10GHZ) <3.0; dielectric loss tangent (10GHZ) ≤0.0020, such as Comparative Example 1, Examples 2-6 have good electrical properties; in addition, it has a low water absorption rate.
[0093] By comparing Comparative Example 1 with Examples 2-6, it can be seen that when the heat-resistant resin polyphenylene ether SA9000 is added to the resin composition, the copper clad laminate prepared by the adhesive has very intuitive and better performance in the TMA copper-containing thermal stratification time test, PCT high-pressure steaming and tinning, 288°C copper-containing sample hot dip tinning, and bonding sheet pressed PTFE core board reflow soldering test. Comparative Example 1 has different degrees of stratification, bursting, blistering and other phenomena in the performance of thermal reliability.
[0094] By comparing Example 2 with Comparative Example 1 and Examples 3-6, it can be seen that the spherical silica filler materials with different particle sizes have a great influence on the thermal expansion coefficient of the copper clad laminate prepared by the glue. The spherical silica with a D50 of 2 microns greatly reduces the thermal expansion coefficient of the substrate, which is better than the spherical silica with a D50 of 3 microns, and reduces the thermal expansion coefficient from more than 100 ppm / K to less than 100 ppm / K. It also characterizes that the preferred filling materials of the present invention are as described in the above table, which provides a resin composition with a low thermal expansion coefficient for the invention.
[0095] In Example 3 and Example 5, the introduction of Caoda SBS-Atype high molecular weight block rubber as a toughening agent significantly improved the glue flow of the bonding sheet, making the glue flow tend to be uniform during the film lamination process, providing better material guidance for the back-end processing and lamination of the bonding sheet. This proves the excellent fluidity of the resin of the present invention.
[0096] The technical scope of the present invention is not limited to the contents in the above description. Those skilled in the art can make various deformations and modifications to the above embodiments without departing from the technical idea of the present invention, and these deformations and modifications should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a high heat-resistant microwave adhesive sheet, characterized in that: Specifically, the prepared glue is evenly applied to both sides of the ceramic filler film, the ceramic film is impregnated on the surface of the glue and then hung on a drying rack, and then placed in an oven and baked at 120° C. for 5 minutes to obtain the bonding sheet; The glue solution comprises, by weight, 9-11 parts of modified polyphenylene ether resin, 4-7 parts of toughening agent, 2-8 parts of elastomer, 2-3 parts of crosslinking agent, 24-68 parts of filling material, 0.05-0.44 parts of initiator and 35-50 parts of toluene; The low molecular weight polyphenylene ether is methyl methacrylate modified polyphenylene ether.
2. The method for preparing the high heat-resistant microwave adhesive sheet according to claim 1, characterized in that: The elastomer includes at least one of XPH-201R, A1535, H1043, SBS-A and P2000.
3. The method for preparing the high heat-resistant microwave adhesive sheet according to claim 1, characterized in that: The toughening agent is any one of B300, MA75 and 1,2-SBS or a combination of two thereof.
4. The method for preparing the high heat-resistant microwave adhesive sheet according to claim 1, characterized in that: The filling material includes 4-5 parts of flame retardant and 20-63 parts of spherical silicon; The flame retardant is any one of mosaflam and SAYTEX-8010; the spherical silicon is any one of SE0047, SE0043 and Q099.
5. The method for preparing the high heat-resistant microwave adhesive sheet according to claim 4, characterized in that: During the preparation process, the 1,2-SBS and A1535 were baked at 50° C. for 15 minutes and then dissolved in toluene.
6. The method for preparing a high heat-resistant microwave adhesive sheet according to claim 1, characterized in that: The glue solution also includes 0.2 parts of a silane coupling agent, the coupling agent is KBM-503, the cross-linking agent is TAIC, and the initiator is BIBP.
7. A high heat-resistant microwave adhesive sheet, characterized in that: Prepared according to the following steps: S1, adding a solvent, a toughening agent, an elastomer, a modified polyphenylene ether resin and a cross-linking agent in sequence and mixing them, adding a filler material and an initiator to the obtained mixture, stirring and homogenizing the obtained glue; S2. The ceramic filler sodium film is glued with the glue liquid by an impregnation process, and then baked in an oven at 120° C. for 300 seconds to obtain a bonding sheet.
8. A high heat-resistant microwave copper-clad laminate, characterized in that: The high heat-resistant microwave adhesive sheet as claimed in claim 7 is used for preparation, and the preparation method thereof is as follows: The baked bonding sheet is cut according to RC, and after copper foil is coated on both sides of the bonding sheet, a plurality of bonding sheets are stacked and placed in a press to complete the plate pressing process.
9. The high heat-resistant microwave copper-clad laminate according to claim 8, characterized in that: In the plate pressing process, the multi-layer bonding sheet is pressed into a copper-clad laminate under a vacuum degree of -0.106 MPa and a pressure of 261-564 psi, with the temperature of the hot plate adjusted to 150-220° C. and the curing time being 200 min.